Acute Effects of Two Different Species of Amyloid-β on Oscillatory Activity and Synaptic Plasticity in the Commissural CA3-CA1 Circuit of the Hippocampus - Cécile Gauthier-Umaña; Jonathan Muñoz-Cabrera; Mario Valderrama; Alejandro Múnera; Mauricio O. Nava-Mesa (Neural Plasticity)
Recent evidence indicates that soluble amyloid-β (Aβ) species induce imbalances in excitatory and inhibitory transmission, resulting in neural network functional impairment and cognitive deficits during early stages of Alzheimer’s disease (AD). To evaluate the in vivo effects of two soluble Aβ species (Aβ25-35 and Aβ1-40) on commissural CA3-to-CA1 (cCA3-to-CA1) synaptic transmission and plasticity, and CA1 oscillatory activity, we used acute intrahippocampal microinjections in adult anaesthetized male Wistar rats. Soluble Aβ microinjection increased cCA3-to-CA1 synaptic variability without significant changes in synaptic efficiency. High-frequency CA3 stimulation was rendered inefficient by soluble Aβ intrahippocampal injection to induce long-term potentiation and to enhance synaptic variability in CA1, contrasting with what was observed in vehicle-injected subjects. Although soluble Aβ microinjection significantly increased the relative power of γ-band and ripple oscillations and significantly shifted the average vector of θ-to-γ phase-amplitude coupling (PAC) in CA1, it prevented θ-to-γ PAC shift induced by high-frequency CA3 stimulation, opposite to what was observed in vehicle-injected animals. These results provide further evidence that soluble Aβ species induce synaptic dysfunction causing abnormal synaptic variability, impaired long-term plasticity, and deviant oscillatory activity, leading to network activity derailment in the hippocampus.